Developmental dynamics of neurotensin binding sites in the human hypothalamus during the first postnatal year - Najimi, Mohamed; Sarrieau, Alain; Kopp, Nicolas; Chigr, Fatiha (Frontiers in Cellular Neuroscience, 2014)
The aim of the present study was to determine a detailed mapping of neurotensin (NT) in the human hypothalamus, during the first postnatal year using an in vitro quantitative autoradiography technique and the selective radioligand monoiodo-Tyr3-NT. Ten human postmortem hypothalami obtained from control neonates and infants (aged from 2 h to 1 year of postnatal age) were used. The biochemical kinetics of the binding in all obtained in this study revealed that the binding affinity constants were of high affinity (in the nanomolar range) and did not differ significantly between all cases investigated. Furthermore, competition experiments show insensitivity to levocabastine and were in favor of the presence of the high affinity site of NT receptor. Autoradiographic distribution showed that NT binding sites were widely distributed throughout the rostrocaudal extent of the hypothalamus. However, the distribution of NT binding sites was not homogenous and regional variations exist. In general, the highest densities were mainly present in the anterior hypothalamic level, particularly in the preoptic area. High NT binding site densities are also present at the mediobasal hypothalamic level, particularly in the paraventricular, parafornical, and dorsomedial nuclei. At the posterior level, low to very low densities could be observed in all the mammillary complex subdivisions, as well as the posterior hypothalamic area. Although this topographical distribution is almost identical during the postnatal period analyzed, age-related variations exist in discrete structures of the hypothalamus. The densities were higher in neonates/less aged infants than older infants in preoptic area (medial and lateral parts). The developmental profile is characterized by a progressive decrease from the neonate period to 1 year of postnatal age with a tendency to reach adult levels. On the other hand, the low levels of NT binding sites observed in posterior hypothalamus did not vary during the first postnatal year. They contrast in that with the very high levels we reported previously in adult. In conclusion, the present study demonstrates the occurrence of high NT binding sites density in various structures in many regions in the human neonate/infant hypothalamus, involved in the control of neuroendocrine and/or neurovegetative functions.